Suspected Ovarian Malignancy in HIV Positive Woman Might Just be Abdominal Tuberculosis: Reports of Two Cases (2020)
Abdominal extrapulmonary tuberculosis (EPTB) responds well to medical treatment. The cases present with features which may be non-specific simulating other diseases like ovarian cancers leading to unnecessary surgery. The EPTB is common among HIV-TB co-infected population. We report cases of abdominal EPTB among 2 HIV positive women mimicking cancer of ovary. Case one was a 41-year-old multiparous HIV positive woman with painless abdominal swelling of a month. Abdomen was distended with ascites and palpable abdominopelvic mass of about 14 weeks size confirmed as a right ovarian 9.8cm x 8.2cm mass on ultrasonography. Investigations showed marked lymphocytosis and CA-125 value of 1095 U/ml. Intraoperatively, there was widespread peritoneal and omental military nodules with adhesion of the colon with the uterus. Histology of specimen showed caseating granulomatous lesion with necrotizing inflammation and cytology of ascitic fluid showed admixture of neutrophil polymorphs, lymphocytes, and macrophages with no malignant cells. She had antituberculosis and responded satisfactorily to the treatment. The second case was a 50-year-old grand-multiparous with recurrent abdominal swelling one month after surgery for suspected ovarian cancer in a private hospital. The histology of surgical specimen did not show malignant cells. The abdomen was distended with ascites and firm irregular 12-14 weeks suprapubic mass confirmed from ultrasonography as a left adnexal complex mass. The Mantoux test and HIV screening were positive. She was treated with antituberculotic and antiretroviral drugs with satisfactory improvement. Conclusion: With the high prevalence of HIV-TB co-infection in our environment, the possibility of abdominal tuberculosis should be considered in HIV positive patients with abdominal mass. This diagnosis should be high in our differentials and use of ancillary investigations can be helpful in resolving this diagnosis to avoid unnecessary surgical interventions.